Infrastructure communication: A systematic literature review - Widianingrum, Ratna; Wahyuni, Hermin Indah; Rahayu (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2024)
In the last few decades, research on communication and development has developed due to the emergence of many development theories in third-world countries. This research aims to determine the research trends in the infrastructure sector from a communication perspective and identify gaps. Papers were selected based on specific words relevant to the issue of development communication and infrastructure communication throughout Indonesia. A total of 33 papers from international and national journals were analyzed to find several paper themes, and analyzed based on categories that emerged from these themes. The analysis results showed that there were only four papers still dominated by development communication. This study also identified gaps in the literature on infrastructure communication, especially those using Niklas Luhmann's Communication Theory. This systematic research (Systematic Literature Review) used the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis) method in which, as found, there has been no research on the theme of infrastructure in the field of communication science specifically looking at how it occurs or how communication on infrastructure communication itself really is. It is important to see the infrastructure problem entirely and cross-sectional subject in a unified system - not as the pieces of events in one research object/area. An understanding of communication issues in infrastructure development will make it easier for various parties to determine future communication.